Thyroid transcription factor 1 and cytokeratins 1, 5, 10, 14 (34βE12) expression in basaloid and large-cell neuroendocrine carcinomas of the lung - Sturm, Nathalie; Lantuéjoul, Sylvie; Laverrière, Marie-Hélène; Papotti, Mauro; Brichon, Pierre-Yves; Brambilla, Christian; Brambilla, Elisabeth (Human pathology, 2001)
Basaloid carcinoma (BC) and large-cell neuroendocrine carcinoma (LCNEC) are 2 recently recognized variants of large-cell lung carcinomas that may overlap in their morphology, and are discriminated by expression of neuroendocrine markers in LCNEC. Because thyroid transcription factor 1 (TTF-1) is expressed in lung adenocarcinomas but not in squamous cell carcinomas (SCC), and 34βE12 recognizes a set of high-molecular-weight cytokeratins characteristic of basal stem cells, we hypothesized that these 2 markers could help in distinguishing BC from LCNEC. Immunostaining for TTF-1 was detected in 40.9% of pure LCNEC but in no BC or basaloid variant of SCC. In contrast, immunoreactivity for 34βE12 was shown in all BC and basaloid variant of SCC but in only 1 LCNEC. Bouin fixation was less efficient than formalin in the immunodetection of both markers for its well-known deleterious effect on antigen preservation. Specificity of TTF-1 for LCNEC (100%) and that of 34βE12 for BC (98.3%) exceeded that of NE markers for distinction of these 2 entities. These data show that TTF-1 and 34βE12, in association with specific neuroendocrine markers, represent a useful panel of antibodies in differentiating carcinomas presenting with a solid pattern, palisading, or pseudorosettes, the expression of TTF-1 excluding the diagnosis of BC, and staining with 34βE12 excluding pure LCNEC. HUM PATHOL 32:918-925. Copyright © 2001 by W.B. Saunders Company